Impact of dizziness on everyday life in older primary care patients: a cross-sectional study - Dros, Jacquelien (BioMed Central, 2011)
BACKGROUND: Dizziness is a common and often disabling symptom, but diagnosis often remains unclear; especially in older persons where dizziness tends to be multicausal. Research on dizziness-related impairment might provide options for a functional oriented approach, with less focus on finding diagnoses. We therefore studied dizziness-related impairment in older primary care patients and aimed to identify indicators related to this impairment. METHODS: In a cross-sectional study we included 417 consecutive patients of 65 years and older presenting with dizziness to 45 general practitioners in the Netherlands from July 2006 to January 2008. We performed tests, including patient history, and physical and additional examination, previously selected by an international expert panel and based on an earlier systematic review. Our primary outcome was impact of dizziness on everyday life measured with the Dutch validated version of the Dizziness Handicap Inventory (DHI). After a bootstrap procedure (1500x) we investigated predictability of DHI-scores with stepwise backward multiple linear and logistic regressions. RESULTS: DHI-scores varied from 0 to 88 (maximum score: 100) and 60% of patients experienced moderate or severe impact on everyday life due to dizziness. Indicators for dizziness-related impairment were: onset of dizziness 6 months ago or more (OR 2.8, 95% CI 1.7-4.7), frequency of dizziness at least daily (OR 3.3, 95% CI 2.0-5.4), duration of dizziness episode one minute or less (OR 2.4, 95% CI 1.5-3.9), presence of anxiety and/or depressive disorder (OR 4.4, 95% CI 2.2-8.8), use of sedative drugs (OR 2.3, 95% CI 1.3-3.8) , and impaired functional mobility (OR 2.6, 95% CI 1.7-4.2). For this model with only 6 indicators the AUC was .80 (95% CI .76-.84). CONCLUSIONS: Dizziness-related impairment in older primary care patients is considerable (60%). With six simple indicators it is possible to identify which patients suffer the most from their dizziness without exactly knowing the cause(s) of their dizziness. Influencing these indicators, if possible, may lead to functional improvement and this might be effective in patients with moderate or severe impact of dizziness on their daily lives.